(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Prevention of wound infection after appendectomy is very important for the post-operative management of the acute appendicitis patients. Objective: The purpose of the present study was to validate the efficacy of local application of metronidazole solution in the wound after closing of peritoneum in the prevention of appendectomy wound infection. Methodology: This randomized control trial was conducted in the Department of Surgery at Rajshahi Medical College Hospital, Rajshahi, Bangladesh from July 2009 to June 2011 for a period of two years. Patients admitted with features of uncomplicated and complicated acute appendicitis (Gangrenous or perforated) underwent emergency appendectomy by grid iron incision in all the units of surgery were selected as study population. The study population were divided into two groups into group A and group B. In group A (treatment group) after closure of peritoneum the exposed tissue was washed and was flooded with 100ml of metronidazole solution with 5 gm/ml concentration and was waited for one minute and in group B (control group) with the same amount of sterile saline solution. All patients were evaluated daily for evidence of wound infection such as fever, unusual wound pain with recording of pulse, temperature. Suspected wounds were checked on 3rd, 5th and 7th POD routinely after removal of dressing. Result: A total number of 200 patients were recruited for this study and was divided into two groups in equal number. Therefore, 100 cases were in group A and the rest of 100 cases were enrolled in group B. The mean age with SD of group A and B were 25.06±9.14 years and 23.82±7.51 years respectively. Uncomplicated appendicitis was found in 66 cases and 70 cases in group A and B respectively (p>0.05). In metronidazole wound wash group only 5 patients developed wound infection, however, in saline wash group 22 patients developed infection. Among the positive cultures Staphylococcus aureus was 3 cases and Escherichia coli was in 7 cases. Conclusion: In conclusion rate of wound infection is less in the group treated with the local application of metronidazole solution after appendectomy Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 54-58